Komunikasi Interpersonal Bidan untuk Mengurangi Ibu dan Neonatal Kematian di Indonesia - Nurhayani (STIKES Columbia Asia Medan, 2024)
The high maternal and newborn mortality rate is a burden for governments globally, considering that the maternal and newborn mortality rate is an indicator of a country's health. Various efforts have been made to reduce maternal and infant mortality rates, including reproductive health literacy, screening programs for pregnant women, improving pregnancy nutrition, and increasing accountability of health workers. This research aims to determine the level of interpersonal communication skills required by midwives, pregnant women and their families. A qualitative research approach using the case study method is used. This research involved six informants from three groups: program creators, program implementers, and program recipients. This research shows that every communicator must improve communication competencies, such as listening effectively, keeping secrets, opening up, and empathizing, to establish successful interpersonal communication between midwives, pregnant women, and the mother's family. Empathy is essential for effective communication between midwives, pregnant women and their families. The empathy in question occurs when communicators understand each other's position and do not force each other's will, giving the impression that the other party is ignoring them. Efforts to save mothers and newborn babies are a responsibility that must be carried out by all parties; This is not only the responsibility of the government, midwives or mothers of newborn babies, but collaboration is needed collaboratively so that efforts to save mothers and newborn babies can have a positive impact and bring about significant change with mutual benefits.